Inflammatory Responses in the Secondary Thalamic Injury After Cortical Ischemic Stroke - Cao, Zhijuan; Harvey, Sean S.; Bliss, Tonya M.; Cheng, Michelle Y.; Steinberg, Gary K. (Frontiers in Neurology, 2020)
Stroke is one of the major causes of chronic disability worldwide and increasing efforts have focused on studying brain repair and recovery after stroke. Following stroke, the primary injury site can disrupt functional connections in nearby and remotely connected brain regions, resulting in the development of secondary injuries that may impede long-term functional recovery. In particular, secondary degenerative injury occurs in the connected ipsilesional thalamus following a cortical stroke. Although secondary thalamic injury was first described decades ago, the underlying mechanisms still remain unclear. We performed a systematic literature review using the NCBI PubMed database for studies that focused on the secondary thalamic degeneration after cortical ischemic stroke. In this review, we discussed emerging studies that characterized the pathological changes in the secondary degenerative thalamus after stroke; these included excitotoxicity, apoptosis, amyloid beta protein accumulation, blood-brain-barrier breakdown and inflammatory responses. In particular, we highlighted key findings of the dynamic inflammatory responses in the secondary thalamic injury and discussed the involvement of several cell types in this process. We also discussed studies that investigated the effects of blocking secondary thalamic injury on inflammatory responses and stroke outcome. Targeting secondary injuries after stroke may alleviate network-wide deficits, and ultimately promote stroke recovery.